Darke - Sage, Angie; Zug, Mark (New York : Katherine Tegen Books, 2011)
Apprentice Septimus Heap must enter the Darke to save the Castle and the Wizard Tower from destruction, but he needs the help of many to battle the spreading Darkenesse.
Keywords: Wizards -- Fiction; Fantasy fiction